Fluid Intelligence as a Mediator of the Relationship between Executive Control and Balanced Time Perspective - Zajenkowski, Marcin; Stolarski, Maciej; Witowska, Joanna; Maciantowicz, Oliwia; Łowicki, Paweł (Frontiers in Psychology, 2016)
This study examined the cognitive foundations of the balanced time perspective (BTP) proposed by Zimbardo and Boyd (1999). Although BTP is defined as the mental ability to switch effectively between different temporal perspectives, its connection with cognitive functioning has not yet been established. We addressed this by exploring the relationships between time perspectives and both fluid intelligence (measured with Raven’s and Cattell’s tests) and executive control (Go/No-go and anti-saccade tasks). An investigation conducted among Polish adults (N = 233) revealed that more balanced TP profile was associated with higher fluid intelligence, and higher executive control. Moreover, we found that the relationship between executive control and BTP was completely mediated by fluid intelligence with the effect size (the ratio of the indirect effect to the total effect) of 0.75, which suggests that cognitive abilities play an important role in adoption of temporal balance. The findings have relevance to time perspective theory as they provide valuable insight into the mechanisms involved in assigning human experience to certain time frames.